(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
The formation of vocational qualities in adolescents is a multifaceted process influenced by social, cognitive, and personal factors. This article explores the social psychological basis of vocational development during adolescence, highlighting the role of social influences, cognitive processes, personal experiences, and educational environments in shaping adolescents’ career aspirations and decisions. By understanding the underlying mechanisms driving vocational development, educators, parents, and policymakers can better support adolescents in exploring their interests, developing their skills, and making informed career choices. Ultimately, investing in the vocational development of adolescents is essential for fostering their future success and contributing to the well-being of society.